SEKOLAH MENENGAH KEJURUAN TEKNIK KOMPUTER DAN INFORMATIKA DI KUBU RAYA - Adam, Kharisma; Zain, Zairin; Pebriano, Valentinus (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Technological developments that continue to evolve changes in various activities such as industries that rely heavily on computers and robot technology to increase industrial production. From this industrial development, it requires competent human resources who can compete in the industrial world. One way to improve human resources in the field of technology is to build a Computer Engineering and Informatics Vocational High School. Improvement and additional facilities are needed to support education in Kubu Raya Regency. The design stages of the Computer and Informatics Engineering Vocational High School in Kubu Raya Regency start from the preparation stage, the analysis stage, the synthesis stage and the design stage. Application of understanding tropical architecture with consideration of the principle of spatial comfort in buildings related to aspects of the body size of the building user, aspects of human space based on human activities in it, audio comfort, visual comfort, and thermal comfort in buildings. The application of renewable energy, such as solar power generation, is applied to building facades to provide electricity sources and block light from entering the room. In addition, the application of laterite brick material and roaster for air humidity adjusts the geographical area of Kubu Raya Regency which is a tropical area. The formation of buildings with a philosophical composition of shapes and room analogies from the Printed Circuit Board gives the meaning of access to rooms that are connected to one another.